VIWITHAN: A STANDARDIZED ASHWAGANDHA EXTRACT AMELIORATES OVALBUMININDUCED AIRWAY-INFLAMMATION AND OXIDATIVE STRESS IN MOUSE MODEL - HS, VASAVI; HV, SUDEEP; ILLURI, RAMANAIAH; K, SHYAMPRASAD (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Withania somnifera, commonly known as Ashwagandha, Indian ginseng, has been used in Ayurvedic and indigenous medicinal preparations for various disease conditions since long time. In the present study, we investigated the protective effects of Viwithan, a standardized proprietary extract from Ashwagandha roots, against airway-inflammation and oxidative stress modulation in an ovalbumin (OVA)-induced murine model of inflammation. Methods: Allergic asthma was initiated in BALB/c mice by sensitizing with OVA on days 1 and 14, followed by intranasal challenge with OVA on days 27, 28, and 29. Mice were administered Viwithan (200 and 400 mg/kg) by oral gavage before challenge. Then, mice were evaluated for the presence of airway inflammation, production of allergen-specific cytokine response, lung pathology, and oxidative stress modulation. Results: The results showed that treatment with Viwithan attenuated OVA-induced lung inflammation in mice. Viwithan significantly attenuated inflammatory cell infiltration into the bronchoalveolar lavage fluid and markedly reduced the levels of pro-inflammatory cytokines, interleukin-10, and transforming growth factor-β1 in lung tissues. Viwithan treatment considerably reduced the lung weight in OVA-sensitized mice. Viwithan markedly attenuated the OVA-induced generation of reactive oxygen species in lung tissues. Conclusion: Together, these results suggested that Viwithan alleviates OVA-induced airway-inflammation and oxidative stress, highlighting the potential of standardized Ashwagandha extract as a useful therapeutic agent for pulmonary fibrosis management.